2020
DOI: 10.1016/j.ufug.2020.126778
|View full text |Cite
|
Sign up to set email alerts
|

Examining the effects of green infrastructure on residential sales prices in Omaha, Nebraska

Abstract: Green infrastructure (GI), practices consisting of using vegetation and soil to manage stormwater runoff (e.g., rain gardens, vegetated roofs, bioswales, etc.), has been adopted by cities across the world to help address aging water infrastructure, water quality, excess water quantity, and urban planning needs. Although GI's contribution to stormwater control and management has been extensively studied, the economic value of its benefits is less known. In Omaha, NE, GI projects have been completed in several p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(5 citation statements)
references
References 49 publications
0
2
0
1
Order By: Relevance
“…Our results confirm that the majority of cases (507 of 547) explicitly link NbS to specific urban challenges. Cases for which this link was missing mostly related to studies focused on ES assessment and economic valuation (e.g., Chen, Wang, Ni, Zhang, & Xia, 2020; Hoover, Price, & Hopton, 2020). In our dataset, the most frequently reported urban challenges include health and well-being, biodiversity loss, and the urban heat island.…”
Section: Discussionmentioning
confidence: 99%
“…Our results confirm that the majority of cases (507 of 547) explicitly link NbS to specific urban challenges. Cases for which this link was missing mostly related to studies focused on ES assessment and economic valuation (e.g., Chen, Wang, Ni, Zhang, & Xia, 2020; Hoover, Price, & Hopton, 2020). In our dataset, the most frequently reported urban challenges include health and well-being, biodiversity loss, and the urban heat island.…”
Section: Discussionmentioning
confidence: 99%
“…The HPM was revised to be widely applied for the monetary evaluation of ecosystem services and natural environments [4]. There are three forms of the HPM, including linear regression, semi-logarithmic regression, and logarithmic regression [2,4,12,18,22,25,[53][54][55][56]. The functional forms of each model are described as follows.…”
Section: Methodsmentioning
confidence: 99%
“…Within focus group discussions and also throughout key literature we found that beyond the radical transformation of social, technical and technical systems, integrated urban water management is often underpinned by pragmatic economic considerations (ECONF) (Alves et al, 2018). BGI has been shown to positively influence property values (Hoover et al, 2020), generate greater tourism amenity (Cook et al, 2019;Whiteoak, 2019), and promote the circular economy (Langergraber et al, 2020).…”
Section: Background: Identifying Critical Factors From Current Researchmentioning
confidence: 95%